Pelatihan Manajemen Biaya Pada Para Pengusaha Kecil dan Menengah Bidang Jasa Sebagai Strategi Mewujudkan Diferensiasi - Murdayanti, Yunika; Gurendrawati, Etty; Perdana, Petrolis Nusa (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2017)
Community service activities are conducted with the aim of providing skills for all small-scale entrepreneurs in the field of services or owners of the rented house in order to be able to calculate the income of how much the number of rented houses they have, and depending on whether the rented house has been in accordance with the set of price included the cost of electricity and water that every month must be paid by the rented house owner. Investment in a rented house is a simple investment, but it must be managed well. Long before you decided to invest in a rented house, it is good to do a survey first. The survey was conducted to find out the gaps and obstacles in managing the rented house business. Investment in a rented house needs management and a lot of time. Sometimes persistence is the key to good home rental management. This can be seen from the opportunities that exist in the investment of house rental is still promising.Participants were trained on tips on managing routine cost controls that occurred both during business and household expenses and trainees were able to understand how to smartly manage spending, payments, and other expenses so they would not find a larger expenditure rather than income.